The Decision-Making Behavior of Air Force Officers and the Management Control Process. - Harrell, Adrian M. (The Accounting Review, 1977)
Abstract ABSTRACT: This paper presents the results of a behavioral experiment which examined two proposals about middle-management decision-making behavior that are incorporated implicitly into Anthony's description of the management control process [Anthony, 1965]. The first of these proposals is concerned with how middle-level managers are motivated and predicts that their management control decisions are influenced strongly by the organizational goals emphasized by their senior managers. The second proposal involves how well middle-level managers can use multiple criteria to make decisions and involves the proposition that they accurately can incorporate a specified importance of organizational goals into their management control decisions. The results of the experiment suggests that Anthony's conceptual framework may be appropriately applied in nonprofit, public sector organizations such as the large military organization where the experiment was performed.